Disadvantages the Legal Effects of Reasoning and Operative Words in Writing a Civil Ruling (An Analytical Study) - Sharqi, Maysara Mohammed; Yassin, Ahmed Samir Mohamed; Ibrahim, Saad Ismael (Journal of Ecohumanism, 2024)
The reasoning for civil judgments and what is said must be done in accordance with legal requirements and conditions that must be met in them, which we mentioned in the second chapter, so that the reasoning and what is said come out with something plausible and acceptable that It is suitable for justifying his ruling and the ruling issued by him in the case before him, so that he becomes able to understand all the elements of the realistic and legal case. Because causation is an obligation on the judge to achieve the goal. Because causation is an obligation on the judge to achieve the goal and the goal he seeks, and in the event of any defect in the causation and what is said, we are faced with a deficiency or contradiction between the reasoning and what is spoken It leads to a deficiency in the justification of judgments, as well as a contradiction between what is spoken and the justification. These two effects have an important consequence on the civil judicial ruling. Because the deficiency in the reasoning means not achieving the full goal intended by the legislator when it is necessary to mention the reasons in the ruling, so it is also called a deficiency in the legal basis of the ruling.